Brain Drain from Turkey to the Usa and Europe: Historical Process and Current Trends - İbrahim Ethem Akyıldız (Coğrafya Dergisi)
This study investigates the historical evolution and current trends of brain drain from Turkey to the United States and Europe. Beginning in the 1960s, this migration has undergone significant transformations driven by socioeconomic and political shifts. Using data from TurkStat, the U.S. Department of Justice and Eurostat, the study highlights key developments such as the rise in H-1B and Green Card applications to the United States in the 1990s and the structured focus of Europe’s Blue Card program on skilled labor. Migration to the United States is primarily associated with technological, scientific, and academic opportunities, whereas Europe’s migration policies have evolved from labor agreements to selective skilled migration programs. This study comprehensively analyzes these dynamics, offering insights into how international opportunities have historically shaped Turkey’s skilled workforce. It concludes with policy recommendations emphasizing academic collaborations, incentives for diaspora engagement and sustainable strategies to mitigate human capital losses and strengthen Turkey’s global competitiveness.